Russian Consumer Sector: Methodology of Evaluation - Agarkov, Gavriil Aleksandrovich; Sudakova, Anastasiya Yevgenyevna (Economy of Regions, 2015)
The article describes the methodology for estimating the Russia’s consumer sector and the effect of its application. The monitoring procedure of the Russian consumer sector groups indicators into two units: the unit of the estimation of consumer goods and the services market estimation unit. The estimation unit of consumer goods is composed of two modules: food products and non-food products. This module offers two components that provide an estimation of the consumer sector: marketing (estimates the accessibility of retail trade and services for end users) and production (estimates the domestic manufacture). The results of the estimation show general improvements in the consumer sector in the period of 2000-2014, but overall development is evaluated as low. The analysis revealed that the financing is growing faster than the quality indices of development. As an example, the financing of agriculture has increased by 1.5 times over 15 years (against comparable prices from 2000), while agricultural production has not changed. Another most pressing challenge is the weak differentiation of the Russian economy, as evidenced by the low rates of non-food production (availability of non-foods of own production remains at a low level and averages 20 %). The results of the estimation suggest the need to reform the regulation of the sector primarily concerning priorities for its development and improvement of financial and economic mechanisms to achieve them.